2020
DOI: 10.1142/s2010326321500362
|View full text |Cite
|
Sign up to set email alerts
|

Boolean cumulants and subordination in free probability

Abstract: Subordination is the basis of the analytic approach to free additive and multiplicative convolution. We extend this approach to a more general setting and prove that the conditional expectation [Formula: see text] for free random variables [Formula: see text] and a Borel function [Formula: see text] is a resolvent again. This result allows the explicit calculation of the distribution of noncommutative polynomials of the form [Formula: see text]. The main tool is a new combinatorial formula for conditional expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…This section is devoted to calculation of the conditional expectation announced in the introduction. We are able to calculate it using Boolean cumulants and results from [10,7], surprisingly calculations which use Boolean cumulants seems to be simpler than the one which use free cumulants. First we will recall relevant facts about subordination functions, for details see [2].…”
Section: Calculation Of Conditional Expectationmentioning
confidence: 99%
See 2 more Smart Citations
“…This section is devoted to calculation of the conditional expectation announced in the introduction. We are able to calculate it using Boolean cumulants and results from [10,7], surprisingly calculations which use Boolean cumulants seems to be simpler than the one which use free cumulants. First we will recall relevant facts about subordination functions, for details see [2].…”
Section: Calculation Of Conditional Expectationmentioning
confidence: 99%
“…Recently discovered connections between Boolean cumulants [7,10] and free probability allows to overcome that difficulty. In particular it was observed that Boolean cumulants appear quite naturally in calculations of conditional expectations of some functions of free random variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will need two formulas involving Boolean cumulants. They can be found in [10] and [12] and were used also in [18]. Proposition 2.6.…”
Section: Freeness and Cummulantsmentioning
confidence: 99%
“…Powerful as it is, subordination itself does not allow to prove all the results which we are studying here. We take advantage of connections between free probability and Boolean cumulants established recently in [10,12]. We develop ideas from [12], in particular we provide a new expansion of the reciprocal of the additive subordination function in terms of Boolean cumulants…”
Section: Introductionmentioning
confidence: 99%